Physical Properties of Cacao Beans - Derry Handrian; Igef Rasinta; Muhammad Robby Farhan; Rommel Siahaan (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
The Cacao beans are widely used as raw material in the chocolate and food industries, where knowledge of their physical properties is essential for post-harvest handling and processing. This study aimed to compare the physical characteristics of mature and raw cacao beans by determining major diameter (Dmajor), moderate diameter (Dmoderat), minor diameter (Dminor), geometric mean diameter (GMD), sphericity, volume, bulk density, angle of repose, and angle of friction. The research was conducted through direct observation and measurement of cacao bean samples in both maturity levels. Data were analyzed by calculating dimensional and physical parameters using standard formulas. The results indicated that mature cacao beans generally had larger dimensional values (Dmajor, Dmoderat, Dminor, and GMD) compared to raw beans, which directly influenced their volume and sphericity. Bulk density of raw beans was relatively higher, while mature beans showed lower density due to reduced moisture content. Furthermore, the angle of repose and angle of friction were higher in raw beans, reflecting stronger resistance to flow and surface contact compared to mature beans. In conclusion, maturity level significantly affects the physical properties of cacao beans, which has implications for their handling, drying, and processing in the cacao industry.